2014
DOI: 10.3389/fnins.2014.00188
|View full text |Cite
|
Sign up to set email alerts
|

Single-sided deafness and directional hearing: contribution of spectral cues and high-frequency hearing loss in the hearing ear

Abstract: Direction-specific interactions of sound waves with the head, torso, and pinna provide unique spectral-shape cues that are used for the localization of sounds in the vertical plane, whereas horizontal sound localization is based primarily on the processing of binaural acoustic differences in arrival time (interaural time differences, or ITDs) and sound level (interaural level differences, or ILDs). Because the binaural sound-localization cues are absent in listeners with total single-sided deafness (SSD), thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 40 publications
4
74
0
3
Order By: Relevance
“…When the first BCI was introduced into clinical practice for SSD, several studies investigated their performance compared to the CROS HA. In reality, the BCI would not restore binaural hearing but, by inducing a phase difference in bone conduction stimulation in the normal-hearing cochlea, it exceeds the disadvantages imposed by the head shadow effect, enhancing the monaural function of the healthy side [10]. Although speech discrimination in noise has been shown to be greatly improved compared with the CROS HA, no great differences were found in terms of improvement for sound localization.…”
Section: Discussionmentioning
confidence: 98%
“…When the first BCI was introduced into clinical practice for SSD, several studies investigated their performance compared to the CROS HA. In reality, the BCI would not restore binaural hearing but, by inducing a phase difference in bone conduction stimulation in the normal-hearing cochlea, it exceeds the disadvantages imposed by the head shadow effect, enhancing the monaural function of the healthy side [10]. Although speech discrimination in noise has been shown to be greatly improved compared with the CROS HA, no great differences were found in terms of improvement for sound localization.…”
Section: Discussionmentioning
confidence: 98%
“…This is attributed to the head shadow effect and the resulting sound level differences that occur for sounds arriving at the impaired ear versus the normal hearing ear(18). Others have shown that some monaural listeners are able to use spectral cues to improve horizontal localization ability, although large inter-subject variability is observed(17). In our clinical experience we have observed that some monaural listeners will anecdotally report perceived localization ability.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, others have demonstrated that monaural listeners can in fact localize in the horizontal plane by using either spectral cues(17) or perceived level differences in the signal as it moves from the impaired ear to the normal hearing ear(18). It is possible that with the increased audibility provided with CROS and BAIs, some localization ability may be restored.…”
Section: Introductionmentioning
confidence: 99%
“…Where sound spectra are more diverse, spectral cues are less reliable, which leads to dependence on changes in proximal sound levels, or the much less precise head-shadow effects (Van Wanrooij and Van Opstal, 2004). In a study of adults with unilateral SPHL, Agterberg et al (2014) attributed much of the inter-subject variability for horizontal plane localization to the varying degrees of high frequency hearing in the better ear of participants. The participants with better high frequency hearing were also better able to use pinna-induced spectral-shape cues of the better hearing ear to aid sound localization.…”
Section: 1 Introductionmentioning
confidence: 99%